A new antimicrobial peptide, Pentatomicin, from the stinkbug Plautia stali - Nishide, Yudai; Nagamine, Keisuke; Kageyama, Daisuke; Moriyama, Minoru; Futahashi, Ryo; Fukatsu, Takema (Scientific reports, 2022)
Antimicrobial peptides (AMPs) play crucial roles in the innate immunity of diverse organisms, which exhibit remarkable diversity in size, structural property and antimicrobial spectrum. Here, we describe a new AMP, named Pentatomicin, from the stinkbug Plautia stali (Hemiptera: Pentatomidae). Orthologous nucleotide sequences of Pentatomicin were present in stinkbugs and beetles but not in other insect groups. Notably, orthologous sequences were also detected from a horseshoe crab, cyanobacteria and proteobacteria, suggesting the possibility of inter-domain horizontal gene transfers of Pentatomicin and allied protein genes. The recombinant protein of Pentatomicin was effective against an array of Gram-positive bacteria but not against Gram-negative bacteria. Upon septic shock, the expression of Pentatomicin drastically increased in a manner similar to other AMPs. On the other hand, unlike other AMPs, mock and saline injections increased the expression of Pentatomicin. RNAi-mediated downregulation of Imd pathway genes ( Imd and Relish ) and Toll pathway genes ( MyD88 and Dorsal ) revealed that the expression of Pentatomicin is under the control of Toll pathway. Being consistent with in vitro effectiveness of the recombinant protein, adult insects injected with dsRNA of Pentatomicin exhibited higher vulnerability to Gram-positive Staphylococcus aureus than to Gram-negative Escherichia coli . We discovered high levels of Pentatomicin expression in eggs, which is atypical of other AMPs and suggestive of its biological functioning in eggs. Contrary to the expectation, however, RNAi-mediated downregulation of Pentatomicin did not affect normal embryonic development of P. stali . Moreover, the downregulation of Pentatomicin in eggs did not affect vertical symbiont transmission to the offspring even under heavily contaminated conditions, which refuted our expectation that the antimicrobial activity of Pentatomicin may contribute to egg surface-mediated symbiont transmission by suppressing microbial contaminants.